Occult gastrointestinal bleeding is a common finding in dogs with chronic kidney disease - Crivellenti, Leandro Z. [UNESP]; Borin-Crivellenti, Sofia [UNESP]; Fertal, Kristi L.; Contin, Catarina M. [UNESP]; Miranda, Caroline M. J. [UNESP]; Santana, Aureo E. [UNESP] (Wiley, 2017)
Background: The risk of occult gastrointestinal bleeding (OGIB) is known to be increased among human dialysis patients suffering from end-stage renal disease. However, there are no studies to date that investigate the incidence of OGIB in either dogs or people with chronic kidney disease (CKD), irrespective of dialysis. Objectives: The purpose of the study was to determine whether the incidence of OGIB is greater in dogs with CKD as compared to a control population, and if this pathology is associated with changes in serum variables related to iron metabolism. Methods: Fecal occult bleeding was evaluated in 10 healthy dogs and 30 CKD dogs. Test results were compared to indicators of blood loss and/or iron metabolism. Results: Dogs with CKD had a significantly higher incidence of OGIB than the control group (P <.0001). While 80% of dogs with stage 2 CKD did not exhibit anemia, 90% tested positive for OGIB. Similarly, subjects with stage 4 CKD had more significant blood loss than either stage 2 (P =.0071) or stage 3 CKD (P =.0385). Serum hemoglobin, transferrin, and iron concentrations in the CKD group were statistically lower than in the control group (P <.0001) and correlated with fecal occult bleeding (r = −.61; r = −.40; r = −.44, respectively), as well as serum creatinine concentrations (P <.0001, r =.64). Conclusions: This preliminary study suggests that OGIB is a common clinical finding among dogs with CKD, even in the early stages of the disease process. Therefore, fecal occult blood tests may be useful as an indication for gastroprotective agents in the treatment plan.
Keywords: Canine; iron metabolism; occult blood loss; screening test